Sistem Sebagai Filsafat (Tawaran Baru Jasser Auda Bagi Pengembangan Hukum Islam Kontemporer) - Akhmad Supriadi (LP2M IAIN Palangka Raya, 2017)
A bomb explosion in the City of London, England, not only shook Jasser Auda’s soul, but also increased the academic anxiety that encouraged him to start writing an important work in his academic career entitled Maqasid al-Shariah as Philosophy of Islamic Law. The peak of his anxiety is a fidgetiness accumulation that he experienced during the struggle with the academic world, especially Islamic law. The condition of Muslims at that time is increasingly culminating in the case of terrorism in London that took the name of Islamic law1 coupled with the low level of muslims human development index (HDI) indicated the inferioity as well as the low quality of Muslims both in terms of science, education, politics, economy, women's empowerment, and other capabilities that were still under of minimum standards2. Jasser Auda also felt an intellectual anxiety when finding the reality of Islamic law (fiqh) seemed to be lacking in solutions to the Islamic community in general. The anxieties here are not related to the material in Islamic law but to the understanding, thought, determination and implementation of Islamic law in the daily lives of Muslims in various countries.